Two new species of freshwater, cave-dwelling crabs of the genus Neostrengeria Pretzmann, 1965, from Colombia (Crustacea: Decapoda: Pseudothelphusidae) - Campos, Martha R. (Zootaxa, 2017)
Two new species of freshwater crabs of the pseudothelphusid genus Neostrengeria Pretzmann, 1965, N. fernandezi n. sp., and N. lassoi n. sp., are described. The genus is endemic to the eastern Andes of Colombia. Neostrengeria fernandezi was collected in Las Cacas cave, Pauna, Boyacá Department and N. lassoi in a stream within Los Aviones cave, La Guadalupe, Santander Department, within the cave as well as in a waterfall outside the cave. With the addition of N. fernandezi and N. lassoi the total number of species of the genus Neostrengeria increases to 27. Like all others species of Neostrengeria, the new species are distinguished primarily by the morphology of the first male gonopod, particularly by the form of lateral, accessory and mesial lobes, outline of the apex, and the mesio-caudal projection of the spermatic channel.